Protocol for exploring the use of hospitals as a learning organisation: a cross-sectional study in South Africa's Eastern Cape province. Issue 2 (22nd February 2023) - Chitha, Nombulelo; Mabunda, Sikhumbuzo A; Essel, Vivien; Funani, Itumeleng; Godlimpi, Lizo; Swartbooi, Buyiswa; Mnyaka, Onke; Thabede, Jahman; Tshabalala, Ruth; Chitha, Wezile
Abstract : Introduction: In today's highly competitive environment, where changes happen at a rapid pace, organisations that stand a chance to survive are those that are proactive and easily adapt to changes. Hospitals are faced with various challenges including scrutiny from stakeholders. This study seeks to investigate learning strategies used by hospitals in one of South Africa's provinces to achieve the principle of a learning organisation. Methods and analysis: This study will employ a quantitative approach using a cross-sectional survey on health professionals of a South African province. Stratified random sampling will be used to select hospitals and participants in three phases. The study will use a structured self-administered questionnaire, designed to collect data on learning strategies used by hospitals to achieve the principle of a learning organisation between June and December 2022. Descriptive statistics (mean, median, percentages, frequency, etc) will then be used to describe the raw data and allow the discovery of patterns. Inferential statistics will also be used to make inferences and predictions about the learning habits of health professionals in the selected hospitals. Ethics and dissemination: The approval to access the research sites with reference number: EC_202108_011 has been granted by the Provincial Health Research Committees of the Eastern Cape Department. Ethical clearance with Protocol Ref no: M211004 has been approved at the Human Research Ethics Committee of the Faculty of Health Sciences at the University of Witwatersrand. Finally, results will be shared with all key stakeholders, including hospital management, clinical staff, through public presentation and direct engagements with stakeholders. The findings may guide hospital leaders and other relevant stakeholders to develop guidelines and policies on creating a learning organisation that contributes to the improvement of quality patient care.